Developing Countries, Tax Treaty Shopping and the Global Minimum Tax - Maarten van 't Riet; Arjan Lejour (CESifo GmbH, 2025)
Analysis of the international network of double tax treaties reveals a large potential for tax avoidance. Developing countries are, on average, not more likely to suffer from tax revenue losses than other countries. Yet, this average masks the fact that several countries, such as Bangladesh, Egypt, Indonesia, Kenya, Uganda and Zambia, are vulnerable to substantial potential losses of withholding tax revenue by treaty shopping. The analysis combines tax parameters of more than a hundred countries with an algorithm from network theory, which simulates the tax minimizing behaviour of multinational enterprises. We introduce the notion of potentially aggressive tax treaties. These are the key treaties in treaty shopping routes, that may lead to substantial tax revenue losses in developing countries. Moreover, the treaty partners are often in a prime position to top-up tax undertaxed profits of developing countries that offer tax incentives to attract investment, thus nullifying the incentive effects.
Keywords: F23; H25; H26; O10; 330; tax treaties; treaty shopping; developing countries; network analysis; withholding taxes; aggressive tax treaties; global minimum tax